AN INTEGRATED MODEL APPROACH WITH FUZZY MULTI CRITERIA DECISION MAKING METHODS FOR THE SELECTION OF THIRD PARTY LOGISTICS FIRM IN THE FOOD INDUSTRY - Nuri Özgür Doğan; Mehri Banu Erdem; Nusret Göksu (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The purpose of this study was to determine third party logistics company selection and evaluation criteria and to help make the most suitable selection among the alternatives in the food sector. Another purpose was to present a mixed model by integrating fuzzy multi criteria decision making methods in third-party logistics company selection process. The combination of fuzzy DEMATEL, fuzzy ANP and fuzzy TOPSIS methods were used in this study. A decision network was created by evaluating the interactions between the criteria determined depending on the decision goal. This study was conducted in a large scale company producing milk and dairy products in food sector. As a result of the analyses made and the findings obtained, technology, delivery performance and quality were found as the criteria having the highest scores in terms of effectiveness. In addition, it was also determined that the most affected criterion among the criteria was the company image. The S2 Company was selected as the best third-party logistics company as a result of the evaluation of alternatives. The integrated fuzzy methods used in this study were used for the first time in the selection and evaluation of third-party logistics companies. And three new criteria; namely, portage price, hygiene and vehicle were added to the related literature which did not exist before.